2013
DOI: 10.2174/156652413805076740
|View full text |Cite
|
Sign up to set email alerts
|

Up-Regulation of MBD1 Promotes Pancreatic Cancer Cell Epithelial-Mesenchymal Transition and Invasion by Epigenetic Down-Regulation of E-Cadherin

et al.

Abstract: Methyl-CpG binding domain protein 1 (MBD1) has been implicated in transcriptional regulation, heterochromatin formation, genomic stability, cell-cycle progression and development. It is also predicted that MBD1 might be involved in tumor development and progression. However, whether and how MBD1 is involved in tumorigenesis, especially in pancreatic cancer (PC), is currently unknown. We found that MBD1 was significantly up-regulated in PC tissues compared with the surrounding normal tissues according to RT-PCR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Pancreatic cancer remains one of the deadliest of all cancers, despite aggressive surgical treatment combined with adjuvant radiotherapy and chemotherapy [9][10][11][12][32][33][34][35][36][37]. Gemcitabine remains to be the standard first line therapy for patients with un-resectable pancreatic cancer [32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pancreatic cancer remains one of the deadliest of all cancers, despite aggressive surgical treatment combined with adjuvant radiotherapy and chemotherapy [9][10][11][12][32][33][34][35][36][37]. Gemcitabine remains to be the standard first line therapy for patients with un-resectable pancreatic cancer [32].…”
Section: Discussionmentioning
confidence: 99%
“…Although FOLFIRINOX has recently been identified as a new regimen for pancreatic cancer (OS 11.1 vs 6.5 of Gemcitabine), the adverse effect is intolerable for many patients [33]. Chemo-resistance and radio-resistance are the principal causes of failure for pancreatic cancer patients to respond to therapy and some studies also suggest that a number of genes or mechanisms are involved in the development of pancreatic cancer [34][35][36][37]. Recombinant methionyl human leptin, an analog of human leptin has been approved by FDA for the treatment of Metabolic Abnormalities associated with Lipodystrophy [1][2][3][4][5][6][7].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that SIRT1 is overexpressed and facilitates acinar to ductal metaplasia in pancreatic cancer (Xu, Zhu, et al, ; Zhao et al, ) and is a positive regulator of tumorigenesis and metastases (Palmirotta et al, ). Also, Deng et al () showed that the silencing of SIRT1 leads to restoration of the expression of E‐cadherin, while N‐cadherin, Snail, and Zeb1 was downregulated in the BxPC‐3 and PANC‐1 cells which decreased cell motility and migration ability in PANC‐1 cells.…”
Section: Sirt1 and Emt Promotionmentioning
confidence: 99%
“…Furthermore, MMP8 facilitates SIRT1‐Zeb1 interaction through association with Zeb1 (Sun et al, ). Also, according to studies, a transcriptional repressor complex including SIRT1, Twist1, and methyl‐CpG binding domain (MBD) protein‐1, can suppress the expression of E‐cadherin (Alivand, Soheili, Pornour, Solali, & Sabouni, ; Xu, Zhu, et al, ) (Figure ).…”
Section: Sirt1 and Emt Promotionmentioning
confidence: 99%
“…7 More detailed studied also revealed that the MBD1 could affect the invasion, metastasis sensitivity of cells to radiation and chemical therapy in PDAC. 31,32 Our study incorporated the MBD1siRNA plasmid into the carbon nanotube carriers to confirm the therapeutic effect in PDAC. However, the similar MBD1 nanoparticles had no specificity to PDAC cells.…”
Section: Discussionmentioning
confidence: 97%